Behavior of pyrene as a polarity probe in palmitoylsphingomyelin and palmitoylsphingomyelin/cholesterol bilayers: A molecular dynamics simulation study - do Canto, António M. T. M. (2015)
Pyrene is a polycyclic aromatic hydrocarbon noted for its remarkable optical spectroscopic properties. Among its uses as a fluorescent probe, measurement of lipid bilayer's equivalent polarity through the pyrene Ham effect stands out. To this effect, the ratio of the intensities of the first and third vibronic bands (I-1/I-3) in its emission spectrum of pyrene is measured. However, issues concerning the precise location of bilayer-inserted pyrene and the possibility of probe-induced perturbation of host bilayer properties are potential sources of concern in this regard. Atomistic molecular dynamics simulations constitute a useful method for the characterization of lipid membrane systems, and, in particular, to understand the behavior of fluorescence probes upon incorporation in lipid bilayers. In this report, we present a detailed characterization of the behavior of pyrene in fluid N-palmitoylsphingomyelin (PSM) and PSM/cholesterol membranes, with emphasis on the degree of proximity between the probe and water molecules inside bilayers, related to the use of pyrene to measure equivalent lipid bilayer polarity. It is concluded that pyrene exerts minor effects on bilayer properties, with slight local disordering being apparent for high cholesterol content. Whereas rotation and lateral diffusion of pyrene are greatly slowed in cholesterol rich systems, its relative transverse location is not significantly affected. While hydration of PSM bilayers, as sensed by pyrene, is already low compared to that of fluid phosphatidylcholine, it becomes even smaller for high cholesterol mole fraction at the studied temperature. (C) 2014 Elsevier B.V. All rights reserved.